14.8k views
2 votes
Write an equation that models the sequence -2, -6, -18, -54, ... A) y = -2x B) y = -2x2 C) y = -3x D) y = -2*3x - 1

User Le Hibou
by
6.1k points

1 Answer

6 votes

Answer:

a(n) = -2*(3)^(n-1)

Explanation:

The sequence -2, -6, -18, -54, ... is a geometric one, since each new term is 3 times the previous term. In other words, 3 is the common ratio.

The general formula for a geometric sequence is

a(n) = a(1)*(r)^(n - 1), where r is the common ratio and a(1) is the first term.

Here,

a(n) = -2*(3)^(n-1)

User Feeeper
by
5.4k points